Opening a Window to the World: Content-based Instruction, Cultural Capital and Critical Pedagogy in an Undergraduate EFL Teaching Program (2017)
This descriptive-interpretative case study examines the impacts on public university pre-service teachers’ cultural capital when exposed to EFL content-based instruction, in this case teaching of the history of the Western hemisphere and related artistic expressions in a two-semester course at a public university in Colombia. After analyzing interviews with students, their writings as well as the researcher’s field notes and interpreting them in the light of content-based instruction, cultural capital and critical pedagogy, it becomes evident that teaching history and related artistic expressions in fact increases students’ cultural capital. This in turn fosters students’ socio-political awareness.